The History of Negative Pressure Wound Therapy (NPWT): From “Lip Service” to the Modern Vacuum System - Miller, Christine (J Am Coll Clin Wound Spec, 2013)
Negative pressure wound therapy (NPWT) is a commonly used modality to facilitate tissue granulation and thus hasten the healing process. While the modern vacuum systems are quite sophisticated, their historic origins can be traced to ancient times. This is a historic review of the precursors to the current negative pressure wound therapy.